PERUBAHAN KAWASAN RUANG TERBUKA HIJAU DI KOTA BOGOR TAHUN 1995-2009 - , PRAYOGA A. PURNAMA, Ir. Suryanto, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to describe the changes in Bogor green open spaces from 1995 to 2009 and to estimate factors that influence such changes. This is a deductive type of research, using qualitative and rasionalistic approach. The study found that changes in a green open space is closely related to the economic sector, industry and increased population. Changes in green open spaces of the city has significants effect on urban development. This research recommends that the supervision and control over the protected areas are cracial as well as consistency in the application of spatial urban planning.